Synergistic efficacy of phage Henu10 with antibiotics against Shigella dysenteriae with insight into phage resistance and fitness trade-offs - Zhao, Jing; Chen, Baohong; Wang, Weizhen; Kang, Yu; Hu, Erli; Zhang, Yuan; Chen, Huiling; Xu, Xiao; Ji, Xinying; Wang, Yuhan; Teng, Tieshan; Gomaa, Salwa E. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe irrational use of antibiotics has facilitated the emergence of multidrug- resistant Shigella spp., undermining the effectiveness of the currently available antibiotics. Consequently, there is an urgent need to explore new approaches, with phage therapy emerging as a promising alternative.MethodsIn this study, we isolated a phage targeting Shigella dysenteriae from sewage samples using DLA methold, designated Henu10. The morphology, biological characteristics, genomic composition, and phylogenetic relationships of Henu10 were thoroughly characterized. To investigate the trade-off relationship between phage resistance and bacterial fitness, phage Henu10-resistant strains R6 and R11 were identified using continuous passage and bidirectional validation methods.ResultsPhage-resistant strains R6 and R11 exhibited impaired adsorption, increased sensitivity to temperature and pH stress, heightened susceptibility to certain antibiotics (such as ciprofloxacin and kanamycin), reduced biofilm-forming capacity, and diminished colonization ability in vivo compared to the wild-type strain.DiscussionThese results indicate that phage Henu10 may effectively control the pathogenic bacteria associated with S. dysenteriae, representing a promising new therapeutic option for treating S. dysenteriae infections.